Pengaruh Pembelajaran Kewirausahaan Terhadap Minat dan Motivasi Berwirausaha Siswa Di Smk Negeri 1 Selong Tahun Pembelajaran 2016 - Huzain Jailani; Muh Fahrurrozi (Universitas Hamzanwadi, 2017)
The purpose of this study was to determine the effect of the interest in entrepreneurship learning and entrepreneurship motivation of students in SMK 1 Selong learning year 2016. The research method used is quantitative method, while the data collection techniques used in this study was a questionnaire, documentation, and observation. Analysis of the data used is descriptive statistical analysis and tested with normality and homogeneity. To test the hypothesis using a simple linearity regression. The results of the study on the first hypothesis is There was a significant effect on the interest in entrepreneurship entrepreneurial learning SMK 1 Selong namely T_hitung = 6,059 with significant value 0.000 0.05, then H_0 H_a rejected and accepted. Great relationship or influence the interpretation of (R) 0.587 with determination R ^ 2 0.344 or 34.4%. The second hypothesis is There was a significant effect on the motivation of entrepreneurship entrepreneurial learning SMK 1 Selong namely T_hitung = 9.080 with 0.000 significance value 0.05, then H_0 H_a rejected and accepted. Great relationship or influence the interpretation of (R) 0.735 with determination R ^ 2 0.451 or 45.1%. The third hypothesis is There was a significant effect on the interest in entrepreneurial learning and entrepreneurship motivation SMKN 1 Selong namely T_hitung = 8.488 with 0.000 significance value 0.05, then H_0 H_a rejected and accepted. Great relationship or influence the interpretation of (R) 0.712 with determination R ^ 2 0.507 or 50.7%. It can be said that entrepreneurial learning has an important role in increasing interest and motivation entrepreneurship class XII students in SMK 1 Selong learning year in 2016.